Design and evaluation of a novel multi-generation system based on SOFC-GT for electricity, fresh water and hydrogen production. (15th April 2020) - Chitgar, Nazanin; Moghimi, Mahdi
Abstract: A novel integrated system is proposed based on solid oxide fuel cell-gas turbine (SOFC-GT) for the simultaneous production of electricity, fresh water and hydrogen. Through a parametric study, the influences of major decision variables on the performance of the system are studied. The energy, exergy and exergoeconomic analysis are conducted. Then, the system is optimized by using the genetic algorithm by taking into account the exergy efficiency, fresh water production rate, hydrogen production rate, and total unit cost of the products as objective functions in three separate optimization problems. Considering the exergy efficiency and total unit cost of the products as the objective functions, the obtained values are 54.2% and 34.5 $/GJ at the optimal point, respectively. Regarding the fresh water production rate and total unit cost of the products as the objective functions, their values at the optimal point are 90.1 m 3 /h and 32.9 $/GJ, respectively. In the case of considering the hydrogen production rate and total unit cost of the product as the objective functions, their values at the optimal point are 11.6 kg/h and 32.8 $/GJ, respectively. Graphical abstract: Image 1 Highlights: A new system based on solid oxide fuel cell (SOFC)-gas turbine (GT) is proposed for power, water and hydrogen production. Energy, exergy and exergoeconomic analysis of a hybrid system is performed. Effect of design parameters on system performance is examined. The hybrid system is optimized by using multi-objective optimization method. The system produces 85.2 m 3 /h fresh water, 10.2 kg/h hydrogen and 4.9 MW power.